KAJIAN KOSMOLOGI PURA DALAM MENINGKATKAN SRADDHA DAN BHAKTI UMAT HINDU DKI JAKARTA (Studi Pura Amerta Jati, Cinere-Jakarta Selatan) - I Made Biasa (Sekolah Tinggi Agama Hindu Dharma Nusantara Jakarta, 2015)
Based on the research I have done that the building of the temple started worshiping phallus shaped palinggih, there Meru and ancestral shrines to gods and ancestral shrines and destructive to the sacred spirits of ancestors. There are also ambiguities in the roof level Meru, Meru for example, there are sacred ancestral spirits rise 7 and 3-storey meru to god. It is physically difficult to distinguish, although the difference is, there is the type of padagingannya. It is what drives Dang Hyang Nirartha make palinggih shaped padmàsana to Hyang Widhi and also distinguish palinggih worship god and the holy spirit ancestors. In a further development of the temple used the word next to the word kahyanganatau parhyangandcngan sense as a holy place to worship Hyang Widhi (with all its manifestations) and bhaþàra or dewapitara the sacred ancestral spirits. Through the temple building is the culmination holiness will be realized, the sanctity of a person's heart would be easier to get closer to the adult Widhi hyang, the devas, Ida bhattara-bhattari sacred and ancestral spirits. With a sense of the people will feel close to his gift and will strive to improve personal holiness, sanctity of the family and the environment by doing self-control. In accordance with the development of the emerging discourse to make the temple not only as a place to worship God in various manifestations, but also as a place of education. Linkage to this study is the lack of understanding by parents about the execution behavior and speech patterns that will be imitated by children. The role of the temple as a place for social activity is the cultivation of ethical values to be adopted by the younger generation. Furthermore, the temple building is a symbol that has a philosophical meaning that describes the existence of a symbol describing the fertility and prosperity, in addition there is a meaning of unity, prosperity and happiness.